Boron Phosphorus Nitride at Extremes: PN6 Octahedra in the High‐Pressure Polymorph β‐BP3N6. (23rd May 2019) - Vogel, Sebastian; Bykov, Maxim; Bykova, Elena; Wendl, Sebastian; Kloß, Simon D.; Pakhomova, Anna; Chariton, Stella; Koemets, Egor; Dubrovinskaia, Natalia; Dubrovinsky, Leonid; Schnick, Wolfgang
Abstract: The high‐pressure behavior of non‐metal nitrides is of special interest for inorganic and theoretical chemistry as well as materials science, as these compounds feature intriguing elastic properties. The double nitride α‐BP3 N6 was investigated by in situ single‐crystal X‐ray diffraction (XRD) upon cold compression to a maximum pressure of about 42 GPa, and its isothermal bulk modulus at ambient conditions was determined to be 146(6) GPa. At maximum pressure the sample was laser‐heated, which resulted in the formation of an unprecedented high‐pressure polymorph, β‐BP3 N6 . Its structure was elucidated by single‐crystal XRD, and can be described as a decoration of a distorted hexagonal close packing of N with B in tetrahedral and P in octahedral voids. Hence, β‐BP3 N6 is the first nitride to contain PN6 octahedra, representing the much sought‐after proof of principle for sixfold N‐coordinated P that has been predicted for numerous high‐pressure phases of nitrides. Abstract : Extreme Bedingungen : α‐BP3 N6 wurde unter kalter Kompression bis zu einem Maximaldruck von 42 GPa in situ untersucht. Anschließendes Heizen mit einem Laser führte zu einer Phasenumwandlung in das Hochdruckpolymorph β‐BP3 N6 . β‐BP3 N6 ist das erste Nitrid, das PN6 ‐Oktaeder enthält, welche ein lange gesuchtes Strukturmotiv in der Grundlagenforschung von Nichtmetallnitriden darstellen.